COUNSELING ON LAW, HEALTH, MSMES AND APPROPRIATE TECHNOLOGY IN PASIR LIMUS VILLAGE, PAMARAYAN DISTRICT: PENYULUHAN HUKUM, KESEHATAN, UMKM DAN TEKNOLOGI TEPAT GUNA DI DESA PASIR LIMUS KECAMATAN PAMARAYAN - Encep Saefullah; Difla Sanaya; Riswan Kamal; Nur Kholifah; Fitri Sofyani; Anil Hotimah; Virda Yulianti Syafkia; Fianto Akbar Nugraha (Yayasan Education and Social Center, 2022)
Phenomena that occur in Pasir Limus Village, Pamarayan District, Serang Regency include: High marriage of minors due to low understanding of community law so that it has the potential for the health of pregnant women and childbirth and divorce, MSME actors who in their production activities still use traditional tools so that they have an impact on sales volume. This service activity aims to provide education to the community in the form of legal and health counseling to provide legal understanding and understanding of the health impacts caused by the marriage of minors, as well as the application of Appropriate Technology (TTG) for MSME actors in Pasir Limus Village to maximize their business. As a result of the implementation of this activity, public knowledge and understanding of law and health has increased, MSME players in their marketing have used online media and product innovations in the form of flavor and packaging variants are increasingly diverse as well as the use of tools with a touch of technology in their production